Central Mini-plication of the Medial Rectus for Convergence Insufficiency. Issue 2 (2nd April 2020) - Merino, Pilar; Mustafín, Ilshat; Gómez De Liaño, Pilar; Cólliga, Carlos
ABSTRACT: Five cases with a mean (± SD) age of 61 (12.02) years are described to study the outcomes of treatment with central mini-plication of the medial rectus (MR) muscles in adult convergence insufficiency with diplopia and near exotropia: mean preoperative deviation: 18 (± 2) pd. Surgical outcome was considered to be favorable when diplopia and symptoms were resolved and final exotropia at near was ≤8 pd at the end of follow-up. A central mini-plication of the medial rectus (MR) muscles was performed in 5 patients (4 unilateral). Overcorrection at distance vision was recorded in 3 cases; this resolved by 3 months postoperatively. There was not overcorrection at near vision in any case. None of the cases operated on had overcorrection at the end of follow-up. The final horizontal deviation was ≤8 pd at near vision, except for 1 case. Symptoms and diplopia resolved in every case but 2/5 required reoperations. The mean follow-up was 8 (2.12) months. Central mini-plication of 1 or 2 medial rectus muscles can improve the symptoms and signs of exotropia associated with convergence insufficiency when exercises and the prisms are rejected by the patients and when these approaches have not solved the problem.